(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Ganderbal town having a population of 28233 as per census 2011 is situated 18 Km north east of Srinagar city. There is no existing sewerage system in the city.Ganderbal District Hospital is under construction at Duderhama, Ganderbal. The total capacity of this hospital is 200 beds but presently working 100 beds only. Ganderbal District hospital has three story building and there are three blocks emergency, labs & OPD. The total area of hospital is 135601 Sq.ft. Nearby this hospital a two storied building nursing college and a mental hospital which are also under constructed. The sanitation system not only deals with environmental issues but here also links to religious activities throughout the town, many religious activities are carried out in the Manasbal Lake area. The rehabilitation of the river will make a positive impact on attracting tourists with a comfortable and sensible culture at the same time. It is not at all easy to evaluate the benefits of providing a proper sanitation system and waste disposal systems in public health, the importance of which is well known. Where wastewater management is inadequate, the cost of healthcare-associated with water-borne diseases is a challenge for public economic resources.